Meningkatkan Minat dan Hasil Belajar Matematika Melalui Model Pembelajaran Problem-Based Learning Siswa SMP Negeri 4 Batam - Rusniati, Rusniati (Nusantara: Jurnal Pendidikan Indonesia, 2023)
Students with low mathematical talent need help in learning mathematics. Therefore, schools must implement various methods to maintain students' interest in mathematics. One method that can be used is Problem-Based Learning (PBL). PBL aims to enhance students' interest and learning outcomes in mathematics. This classroom action research aims to improve learning and strengthen mathematics learning outcomes. The subjects of this study are 39 students from class IXG of SMP Negeri 4 Batam, in the odd semester of the academic year 2022/2023, comprising 21 female students and 18 male students. The data collection instruments used are observation sheets and mathematics learning outcome tests. Data from the observation sheets are analyzed descriptively narratively, while data from the mathematics learning outcome tests are analyzed descriptively statistically. The analysis results show an improvement in the learning process from pre-action to cycles I and II. The implementation of PBL achieved a good category with an increase of 4.10 points. The average score in cycle I was 76.94 and increased to 81.52 in cycle II. Thus, it can successfully enhance students' interest and learning outcomes in mathematics. This is evident from the attainment of the learning mastery target of 70 and the classical learning outcomes that reached or exceeded 85%.